Parkinsonia aculeata L. recorded as alien species in natural habitats of Egypt: Potential for naturalization, invasion or utilization! - Halmy, Marwa Waseem A.; Yasien, Asmaa Ahmed; Sheded, Mohamed Gabr (Phytotaxa, 2024)
Parkinsonia aculeata L. is native to South America and was recorded for the first time in Egypt in the wild. It was recorded in vegetation survey of Elephantine Island in Aswan Governorate in 2020, then it was recorded in Dakhla Oasis in the Western Desert in 2023. The species identity was confirmed by a comparative macromorphological study between the collected specimens and herbarium specimens from other countries, and live specimens cultivated in Antoniades Botanic Garden in Alexandria. The occurrence of this species in the natural habitats of Egypt represents an important disjunction of the biogeographic relevance and raises concerns. The species may cause negative impacts to native species, outcompeting species of the same functional group, or can increase fire hazards in the invaded areas. Taking into consideration that the species has already been naturalized in some countries, its further expansion in Egypt is a possibility. It is of great concern to monitor and control the spread of the species in Egypt and possibly promote an early eradication. Notes on the habitat in which the species has been recorded and its invasive status in Egypt and surrounding nations are discussed.